Development of a Model for the Professional Competence of Middle Managers in the Educational Administration Headquarters - Zobeiri, Hassan; Kordestani, Fereshteh; Saeedi, Leila (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Objective: This research aimed to develop a model for the professional competencies of middle managers in education, including general managers, their deputies, heads of centers, and their deputies. Methodology: The research method was qualitative and aimed at practical application. The research population included all academic experts in educational management, general managers, their deputies at the headquarters level of education, all related studies, research, and articles, as well as relevant documents and laws. A sample of 9 managers and 7 experts, 70 articles, books, or research, and 4 relevant documents and laws were selected through purposive sampling. Data were collected using a document review form for studies, research, articles, and regulations, as well as a semi-structured interview form. Data analysis was performed using thematic analysis and MAXQDA software. Findings: According to the findings of this research, the most important components of professional competence for middle managers in education include 10 main categories derived from 62 subcategories: Personal Skills, Interpersonal Skills, Work Competencies, Global Mindset, Aspiration for Excellence, General Managerial Ability, Professional/Advanced Management Skills, Resource Management, Specialized Knowledge, and Success Enabling. These categories were ultimately presented in the form of a model. Conclusion: It can be concluded that the model of professional competence for middle managers in the headquarters area of education is capable of examination and can be used by educational system planners.